Mineralized tissues in Characiformes: systematics assessment of the morphological variation of the oral dentition and skeletogenesis - Giovannetti, Victor (2019)
The dentition is a character complex recognized for being highly informative for systematic studies for the order Characiformes, hence the dentition was widely explored in systematic studies of several lineages within the order. However, detailed systematic studies that discuss the observed variation in the context of the order as a whole are still scarce. In a similar manner the despite the wide knowledge produced about the adult skeleton of the representatives of the Characiformes, detailed information about the development of this anatomical complex, as well as about the sequence of ossification of the complete skeleton of representatives of the Characiformes are still scarce and to this date there is only one complete sequence of ossification available in the literature. We herein present a detailed study on the dentition of the Characiformes contemplating tooth morphology, tooth implantation mode and implantation position, arrangement of teeth on each bone, formation mode of replacement teeth and the chronological pattern of the replacement. Detailed descriptions are provided for 78 species of Characiformes. with representatives from all recognized families, except for the recently described Tarumaniidae. Fifty-nine characters are proposed, including reinterpreted characters previously proposed in the literature, along with original characters. The variation and distribution of the proposed characters in the Characiformes is discussed along with the proposal of new interpretations of the identity and homology of tooth rows in the premaxilla in representatives of the order. Descriptions of ontogenetic variation of dentition in selected characiform species are provided. Possible additional synapomorphies related to the dentition are proposed for the Anostomidae, Heterocharacinae and Serrasalminae. Two patterns of replacement within the Characoidei are identified and described in detail. Alternative interpretation for the identity and homology of the three tooth rows on the premaxilla present in Brycon, Triportheus and Chalceus is presented along with a proposal of homology of the single premaxillary tooth row present within the Characoidei and Citharinoidei. Also, we herein studied the skeletal development of the small sized characid Astyanax lacustris and the ctenoluciid Ctenolucius hujeta presenting the ossification sequence of the complete skeleton for both species. This study was based on 111 specimens of A. lacustris (2.9 mm NL to 27.6 mm SL) and 100 specimens of C. hujeta (3.5 mm NL to 35.5 mm SL). Specimens were cleared and double stained and the presence of an ossification was scored whenever mineralization was detected. For both species the first ossifications to appear were the tooth plates associated to ceratobranchial 4 and pharyngobranchial 4, the cleithrum and the opercle at 2.9 mm NL for A. lacustris and 3.5 mm NL for C. hujeta. Comparative analyses were conducted for the sequences of A. lacustris, C. hujeta and the already published sequence of S. brasiliensis. The sequences are compared within osteological complexes for the sequence within that complex and in the context of the entire sequence. Differences were observed regarding the sequence of ossification within an osteological complex; the relative intervals between the ossification of the first and last element in an osteological complex, as well as shift of an entire osteological complex in the complete sequence